Quantifying Dam‐Induced Fluctuations in Streamflow Frequencies Across the Colorado River Basin. Issue 10 (18th October 2021) - Hwang, Jeongwoo; Kumar, Hemant; Ruhi, Albert; Sankarasubramanian, Arumugam; Devineni, Naresh
Abstract: Periodic fluctuations in natural streamflow are a major driver of river ecosystem dynamics and water resource management. However, most U.S. rivers are impacted both by long‐term hydroclimatic trends and dams that alter flow variability. Despite these impacts, it remains largely unexplored how dams affect the dominant frequencies of natural streamflow over a highly regulated river network. We investigated the entire Colorado River Basin (CRB) to understand how the annual (10–14 months) and multi‐annual (24–60 months) frequencies in natural flow regimes have been progressively altered by dams. Given the significant alteration over the CRB, we captured changes in streamflow frequencies between naturalized and observed monthly flows via wavelet analysis. Based on the similarity of changes in streamflow frequencies (annual and multi‐annual) over the last 30 years, sections of the riverine network were classified into four groups. The annual frequency was relatively well preserved downstream of Hoover Dam, while showing a systematic trend of alteration downstream of Glen Canyon Dam until Hoover Dam. Meanwhile, the multi‐annual frequency component was highly altered for the entire Lower Colorado main stem (i.e., downstream of Glen Canyon). We also identified dams with significant impacts on streamflow frequency by comparing wavelet coherence estimates. This study advances the notion that dams fundamentally alter river flow regimes across multiple frequencies and with varying amplitudes over time and space, with alteration propagating – or being dampened – by both hydroclimatic fluctuations and water resource management. Key Points: Temporal changes in streamflow frequency are explored in the Colorado River Basin Magnitude of frequency alteration changes with annual frequencies recovering and multi‐annual remaining altered across the river network Dams that significantly alter streamflow frequencies exist across the entire network, and more so in the Lower Colorado Basin